Combined effects of Yupingfeng and metformin on blood glucose levels and intestinal tissue in high-fat diet-induced type 2 diabetic rats - Liu, Hui; Guan, Yuan; Xu, Like; Hu, Ji (Frontiers in Endocrinology, 2025)
This study investigated the effectiveness of a high-fat diet (HFD) in inducing type 2 diabetes in Sprague–Dawley (SD) rats and evaluated the combined therapeutic effects of Yupingfeng and metformin on glycemic index and intestinal histology. A total of 60 SD rats, equally divided by sex, were randomly allocated to six groups. Body weight was measured weekly, and food intake was recorded. During the initial phase of model induction, blood glucose levels increased significantly, exceeding 17.26 mmol/L by week 8, which was significantly higher than that of the control group (p< 0.01). The experimental group received treatment for a total of 7 weeks. Beginning in the third week, the combined administration of Yupingfeng and metformin significantly reduced fasting insulin levels, blood glucose concentrations, and insulin resistance compared to the control group, with further marked reductions observed by the seventh week (p< 0.01). Lipid metabolism indicators, including triglycerides (TG), total cholesterol (TCHO), high-density lipoprotein cholesterol (HDL-c), and low-density lipoprotein cholesterol (LDL-c), showed significant reductions in the treatment groups (p< 0.01). Liver and kidney function assessments showed that the combination therapy exhibited superior safety compared to single-drug treatments. In addition, hematoxylin and eosin (H&E) staining revealed that HFD-induced diabetes caused inflammatory changes in the duodenum and colon. However, the combination therapy markedly alleviated inflammatory symptoms. Overall, the combined treatment significantly improved blood glucose levels, biochemical parameters, and intestinal tissue integrity.